Conflitos regulatórios no transporte de gás natural - Barroso Neto, Abílio das Mercês (2008)
This dissertation regards to the principal regulator conflicts in natural gas transport (movement) area in Brazil, especially with reference to the limit that exists between the regulator competency of Petroleum National Agency, Natural Gas and Biofuels (PNA) and Regulator State Agencies. This broaching was made in according to the legislation, doctrine, juridical and administrative processes and technical studies, relating about the conflicts in transporting of natural gas piping area and the conflict concerning to the gas movement through Liquefied Natural Gas (LNG). On reflects also about regulator practice that it must be harmonized with the Brazilian State purposes, in searching for Common Well in favour of all society. On evidences that, in order that objective be attained, the State must find out instruments more efficient to fortify the gas industry and it can develop in favour of society, accomplishing, this way, the Efficiency Constitutional Principle. Besides, the regulation was inserted in the ambit of Brazilian State reforms, and their evolutive trajectory was observed; on verified, however, that it is showed in a rarefied manner in natural gas industry. This fact propitiates the imperative regulator improvement to the sector, so it is certified the necessity of edification of a clean and stable regulator mark. Actuality and relevance of the theme are evidenced, once the natural gas industry assumes character more and more important in national energetical matrix. Moreover, the mitigation of gas emission greenhouse effect and the necessity of Brazil energetical supply contribute to the national development. Actually, it got greater distinction with the presentation of Gas Law projects in National Congress. So, proposals for natural gas transport (movement) sector were especially analyzed, indicating, even so, divergences between Lay Projects and the necessity of legislator to respect and obey the Federal Constitution, its objectives, principles and federatives competences